FUNGSI BAHASA DALAM SYAIR BIDASARI: KAJIAN SOSIOPRAGMATIK - Fauzi, Mohd (Universitas Lancang Kuning, 2015)
This writing deals with language functions which adops Leech concepts who uses five language functions. By using those concepts, this writing analyzes